Rapeseed transcription factor BnaC9bHLH35 promotes root growth and improves nitrogen use efficiency under low nitrate conditions - Qin-Xin Fang; Haokun Cheng; Zhongni Ma; Qiuyan Xu; Huanpeng Wang; Yunru Yan; Mengting Sun; Rui Wang; Wenlong Liu; Saeed Ullah; Yuhang Fan; Chunchun Huang; et al. (Theoretical and Applied Genetics, 2025)

FHB resistance conferred by Fhb1 is under inhibitory regulation of two genetic loci in wheat (Triticum aestivum L.) - Guoqiang Li; Yang Yuan; Jiyang Zhou; Rui Cheng; Ruitong Chen; Xianmin Luo; Jinxing Shi; Heyu Wang; Boyang Xu; Youyu Duan; Jinkun Zhong; Xin Wang; et al. (Theoretical and Applied Genetics, 2023)

Positional cloning identified HvTUBULIN8 as the candidate gene for round lateral spikelet (RLS) in barley (Hordeum vulgare L.) - Dandan Qin; Gang Liu; Rui Liu; Chunchao Wang; Fuchao Xu; Qing Xu; Yu Ling; Guoqing Dong; Yanchun Peng; Shuangtao Ge; Ganggang Guo; Jing Dong; et al. (Theoretical and Applied Genetics, 2023)
Key message Map-based cloning, subcellular localization, virus-induced-gene-silencing and transcriptomic analysis reveal HvTUB8 as a candidate gene with pleiotropic effects on barley spike and leaf development via ethylene and chlorophyll metabolism. Abstract Barley lateral spikelet morphology and grain shape play key roles in grain physical quality and yield. Several genes and QTLs for these traits have been cloned or fine mapped previously. Here, we report the phenotypic and genotypic analysis of a barley mutant with round lateral spikelet (rls) from cv. Edamai 934. rls had round lateral spikelet, short but round grain, shortened awn, thick glume and dark green leaves. Histocytologic and ultrastructural analysis revealed that the difference of grain shape of rls was caused by change of cell arrangement in glume, and the dark leaf color resulted from enlarged chloroplast. HvTUBULIN8 ( HvTUB8 ) was identified as the candidate gene for rls by combination of RNA-Seq, map-based-cloning, virus-induced-gene-silencing (VIGS) and protein subcellular location. A single G-A substitution at the third exon of HvTUB8 resulted in change of Cysteine 354 to tyrosine. Furthermore, the mutant isoform Hvtub8 could be detected in both nucleus and cytoplasm, whereas the wild-type protein was only in cytoplasm and granular organelles of wheat protoplasts. Being consistent with the rare phenotype, the “A” allele of HvTUB8 was only detected in rls , but not in a worldwide barley germplasm panel with 400 accessions. VIGS confirmed that HvTUB8 was essential to maintain spike integrity. RNA-Seq results suggested that HvTUB8 may control spike morphogenesis via ethylene homeostasis and signaling, and control leaf color through chlorophyll metabolism. Collectively, our results support HvTUB8 as a candidate gene for barley spike and leaf morphology and provide insight of a novel mechanism of it in barley development.

A functional chromogen gene C from wild rice is involved in a different anthocyanin biosynthesis pathway in indica and japonica - Weihua Qiao; Yanyan Wang; Rui Xu; Ziyi Yang; Yan Sun; Long Su; Lizhen Zhang; Junrui Wang; Jingfen Huang; Xiaoming Zheng; Shijia Liu; Yunlu Tian; et al. (Theoretical and Applied Genetics, 2021)

Fine mapping and identification of a novel locus qGL12.2 control grain length in wild rice (Oryza rufipogon Griff.) - Lan Qi; Yingbin Ding; Xiaoming Zheng; Rui Xu; Lizhen Zhang; Yanyan Wang; Xiaoning Wang; Lifang Zhang; Yunlian Cheng; Weihua Qiao; Qingwen Yang (Theoretical and Applied Genetics, 2018)

Genetic and transcriptomic analyses of lignin- and lodging-related traits in Brassica napus - Lijuan Wei; Hongju Jian; Kun Lu; Nengwen Yin; Jia Wang; Xiujian Duan; Wei Li; Liezhao Liu; Xinfu Xu; Rui Wang; Andrew H. Paterson; Jiana Li (Theoretical and Applied Genetics, 2017)

Characterization of OsMIK in a rice mutant with reduced phytate content reveals an insertion of a rearranged retrotransposon - Hai-Jun Zhao; Hai-Rui Cui; Xiu-Hong Xu; Yuan-Yuan Tan; Jun-Jie Fu; Guo-Zhen Liu; Yves Poirier; Qing-Yao Shu (Theoretical and Applied Genetics, 2013)

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)